Aplicación de análisis de datos e investigación forense para la mejora continua y prevención de riesgos desde la perspectiva de auditoría externa - Rodriguez Patiño, Alex Rogelio (2022)
This work details the activities performed over my years of working experience. During this time, I have been capable of developing my technical and management abilities learned during my time as a university student. Also, I have been able to learn about new activities and processes which rely heavily on the use of different technologies to improve businesses and prevent risks. Since my first work experiences, I have been able to get involved in database administration and support from processing tools, from simple macros and spreadsheets to specialized data science and analytics software. I learned different data science techniques such as regression and classification models, anomaly detection and clustering, with the opportunity to apply models in different datasets. Through the years, I was also able to learn new topics, including financial audit, e-discovery, and forensic data analysis. A. Rodriguez • 2 I started leading and managing teams with the support of different tools in a way that I can guarantee a good working environment, which I consider is key to obtain good results without work overload. I have had the opportunity to continue learning and to obtain different certifications related to my working activities. Additionally, it is important to set a learning plan, for which I have some short- and long-term learning objectives. Finally, during my years working, I have always considered the ethics and integrity that every person must have to work in an honest way. This way I can guarantee the safety and confidentiality of the information in my reach. The information that companies possess is a considerable source of opportunities, and with the support of Data Analytics, it is possible to establish a consistent plan and develop processing data models.